The Effect of Maternal Weight Gain in the First and Second Trimesters on the Risk of Developing Preeclampsia in the Third Trimester - Sofiyati, Sofiyati (International Journal on ObGyn and Health Sciences, 2025)
Preeclampsia remains one of the leading causes of maternal and fetal morbidity and mortality worldwide. While its exact etiology is multifactorial, recent studies have pointed to early gestational weight gain as a potential predictor. This study aims to analyze the effect of weight gain in the first and second trimesters on the risk of preeclampsia in the third trimester. A quantitative observational study was conducted using a retrospective cohort design. Medical records of pregnant women meeting the inclusion criteria were reviewed, focusing on weight gain data in the first and second trimesters, and the occurrence of preeclampsia in the third trimester. Statistical analysis was employed to determine the correlation and threshold levels associated with increased risk. The findings indicate a significant association between excessive weight gain during the first and second trimesters and the incidence of preeclampsia in the third trimester. Women who gained more than 5 kg in the first trimester or exceeded 0.5–0.6 kg per week in the second trimester showed a notably higher risk. The pattern suggests that early metabolic and vascular changes may be triggered by rapid weight gain, contributing to the pathophysiology of preeclampsia. Weight gain during early pregnancy, especially when exceeding recommended guidelines, is a critical risk factor for preeclampsia. Monitoring trimester-specific weight gain should be integrated into routine antenatal care to allow early identification and prevention strategies. Public health interventions focusing on maternal nutrition and education can further support the reduction of preeclampsia incidence.